Oral health care among pregnant women in a local primary care institution in Kuantan Pahang- A Preliminary report - Jamani, Nurjasmine Aida; Abllah, Zurainie; Abd. Aziz, Karimah Hanim (2016)
Oral health problem pregnant women is associated with preterm birth and low birth weight.